Revealing the unfavorable role of superfluous CH3NH3PbI3 grain boundary traps in perovskite solar cells on carrier collection. Issue 86 (2nd September 2016) - Du, Yangyang; Cai, Hongkun; Wen, Hongbin; Wu, Yuxiang; Li, Zhenglong; Xu, Jian; Huang, Like; Ni, Jian; Li, Juan; Zhang, Jianjun
Abstract : In this work, the perovskite films with controllable grain size are obtained by a facile method. And the unfavorable role of perovskite grain boundary traps is unveiled by the combination of experiment and simulation analysis. Abstract : In this work, a facile sequential thermal evaporation strategy in low vacuum (STELV) is proposed to achieve good crystallization of CH3 NH3 PbI3 films with controllable grain size. Through a comparative study, it is observed that the photovoltaic parameters of perovskite solar cells (PSCs) are closely related to the CH3 NH3 PbI3 grain size, and large grains should contribute to a superior performance and a small hysteresis index. Also, we demonstrate that the declining performance can be ascribed to a high carrier combination rate caused by superfluous perovskite grain boundary (PGB) traps. By combination with Silvaco simulation software based on physical models, the recombination rate distribution within PSCs is clearly observed. In addition, the lateral conduction band energy distribution within CH3 NH3 PbI3 films and the transient carrier collection efficiency are also displayed, suggesting that PGB traps are prominently responsible for inferior device performance by causing serious lateral transport of photo-generated carriers and reducing their collection efficiency, which is consistent with experimental results.